SIMULATION TRAINING IN MEDICINE: THE STATE AND DIRECTION OF DEVELOPMENT OF SIMULATION TRAINING AT THE TASHKENT MEDICAL ACADEMY - Parpibaeva, D.; Salaeva , M.; Salimova , N.; Abdurakhmanova , L. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Doctors should acquire practical skills in applying clinical situation for patients with patients in simulation departments equipped with high-tech simulators and computerized mannequins, computer games and programs that allow simulating clinical and organizational situations. One of the prerequisites for the implementation of this invention is the creation of modern simulation centers. The article deals with the problems that need to be solved for the successful and effective use of simulation training in vocational education. The chronology of medical modeling is given, in which there are many thousands and inextricably dangers with the possible development of knowledge, the progress of scientific and technological progress and military orders. The purpose of our study is to review the chronology of simulators and the achievements of modern simulator centers. The research methods were theoretical methods; simulation educational technologies; observation; method of scientific analysis.